Brazil in the seventies - Roett, Riordan (Washington : American Enterprise Institute for Public Policy Research, 1976)
This book examines aspects of the political and economic development of Latin America's largest nation. In this volume, four prominent North American scholars have written extensively on Brazilian economic development and raises questions about the course of its future growth and distribution.
Includes bibliographical references.
rpm 11/04/2017
Loans
Keywords: Brazil - Economic conitions - 1945; Brazil - Foreign economic relations; Brazil - Foreign relations - 1930; Brazil